Hypoglycemic episodes among type 1 diabetic patients in Unaizah, Saudi Arabia: causes, management, and associated factors - S.K.S. Aldekheel; M.A.S. Shahin (Сахарный диабет, 2024)
BACKGROUND: Diabetes mellitus is a prevalent condition in Saudi Arabia, with approximately 20% of the adult population affected, ranking sixth highest in the world. This disease is associated with both acute and chronic complications. Among these complications, hypoglycemia is particularly dangerous and can occur during diabetes treatment. Individuals diagnosed with type 1 diabetes may experience multiple episodes of asymptomatic or symptomatic hypoglycemia per week.AIM: To assess the frequency of hypoglycemic episodes and identify associated factors among individuals with type 1 diabetes in Unaizah City, Saudi Arabia.MATERIALS AND METHODS: A quantitative, cross-sectional, descriptive research design was employed in April and May of 2023. A convenience sample of 280 type 1 diabetic clients living in the Qassim region of Unaizah City was selected. Participants completed an electronic structured questionnaire that collected information on sociodemographic factors and hypoglycemia-related data. Descriptive statistics and a Chi-square test were used for data analysis, utilizing SPSS version 23. Ethical considerations were strictly adhered to throughout the study.RESULTS: The findings revealed that over two-thirds of the participants (72.1%) reported experiencing hypoglycemic episodes within the past week. Furthermore, more than one-fifth of these individuals attributed the cause of the episodes to high insulin doses (21%). Seeking medical assistance to change medications for hypoglycemia was reported by more than half of the participants (55.4%), while less than half received help from others during hypoglycemic episodes (42.9%). It was observed that adherence to diabetic medication was higher than adherence to diabetic diet and exercise regimens. Males, as well as single or divorced participants, reported a higher frequency of hypoglycemic episodes. Additionally, patients with higher levels of education and those residing in rural regions reported a higher exposure to hypoglycemic episodes.CONCLUSION: The effective management of hypoglycemia necessitates patient education and awareness regarding its causes and symptoms. Targeted interventions are required to improve adherence to therapeutic regimens and lifestyle modifications. Furthermore, when managing hypoglycemia, it is important to consider the gender, marital status, educational level, and residence of diabetic patients.